Movimento estudantil e repressão política: o Ato Público na Pontifícia Universidade Católica de São Paulo (1977) e o destino de uma geração de estudantes - Cancian, Renato (2008)
This study examines the university student movement of the 1970s and the Public Act at the Pontifical Catholic University of São Paulo (PUC-SP) in 1977, culminating in an episode of police violence against the students. The focus of the search fell on the path of life of a group of former student activists in order to understand, first, how they are linked and part of the student movement, and secondly, if the experience of participation in student movement was able to generate some influence or socialization in terms of political and professional after entering the stage of university education of ex-militants. Theoretically, this study establishes a dialogue with the sociological approaches that focus on the radical student collective actions and roles of young people, and is back to understanding the changes in the patterns of militancy that might occur in the transition from juvenile to life adulthood and integration into the world of work. The methodology of the History of Life provided the basis for the analysis of the biography of former student activists, and from that methodological feature found that the political militancy was a determining factor of student activism and, consequently, a more active participation in the movement university student. The study showed that after training and shutdown of the student movement, the former student activists have continued the practice of political militancy and experience of participation in the student movement has strong influence in their career options.